2007
DOI: 10.1111/j.1365-2133.2007.08305.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus-associated increase in p16INK4A expression in penile lichen sclerosus and squamous cell carcinoma

Abstract: Background Human papillomaviruses (HPVs) are sexually transmitted human carcinogens that may play a role in the oncogenesis of penile cancer. Objectives To investigate the role of HPV infection and expression of the tumour suppressor protein p16 INK4A in the pathogenesis of penile cancer. Methods By means of polymerase chain reaction amplification and reverse hybridization line probe assay to detect HPV infection, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 35 publications
8
60
3
Order By: Relevance
“…Within their series there was only one case of verrucous carcinoma, and it was HPV6-positive, however, this tumour did not express p16 INK4A protein, exhibit p16 INK4A promoter methylation or BMI-1 staining, which suggests additional mechanism of p16 INK4A inactivation. Study by two of the authors of this paper 20 confirmed the inverse correlation between HPV16/18 and p16 INK4A in usual type squamous cell carcinomas and penile lichen sclerosus. We found the same correlation in our usual type samples but not in verrucous, which again suggests the connection to HPV infection only in usual type carcinoma.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Within their series there was only one case of verrucous carcinoma, and it was HPV6-positive, however, this tumour did not express p16 INK4A protein, exhibit p16 INK4A promoter methylation or BMI-1 staining, which suggests additional mechanism of p16 INK4A inactivation. Study by two of the authors of this paper 20 confirmed the inverse correlation between HPV16/18 and p16 INK4A in usual type squamous cell carcinomas and penile lichen sclerosus. We found the same correlation in our usual type samples but not in verrucous, which again suggests the connection to HPV infection only in usual type carcinoma.…”
Section: Discussionsupporting
confidence: 68%
“…Validated samples were tested for the presence of HPV DNA by a broadspectrum HPV PCR method using SPF10 primers, which amplify a 65-bp fragment of the L1 open reading frame and HPV genotypes identified by the INNO-LiPA line probe assay (Innogenetics NV, Ghent, Belgium). 20 As a positive control, a known HPV-positive cervical cancer sample was used. Mouse tissue served as negative control.…”
Section: Hpv Analysismentioning
confidence: 99%
“…Maehama and colleagues [33] reported that they found 10.6% of positive for HPV in women with normal cytology smear, using PCR technique. Based on that report, we expected to find some expression of p16 protein in this group of patients, which may not have happened because of the small number of cases studied, or non-viral integration in the genome of the host [16,18].…”
Section: Discussionmentioning
confidence: 99%
“…The Ki-67 is a marker of protein, non-histonic of cell proliferation, and is expressed in all phases of the cell cycle, except in G0 [18,19]. This protein has a function of growth in human tumor, and expression of its marker could suggest the degree of malignancy [20][21][22].…”
Section: Ki-67mentioning
confidence: 99%
“…Cells with anti-p16 antibody-stained nuclei and/or cytoplasm were considered as positive, irrespective of the intensity of the staining. The grading of the immunohistochemical expression was assessed, according to the method of Prowse et al [29], by grading the intensity (0, negative; 1, low intensity; 2, mild range; and 3, high intensity) and the percentage of positively stained cells (1, low percentage coverage, <30%; 2, mild percentage coverage, 30-60%; and 3, high percentage coverage, more than 60%). The combined score total was calculated as the sum of the intensity and percentage coverage scores.…”
Section: Preparationmentioning
confidence: 99%